PREPARATION AND TRIBOLOGICAL PROPERTIES OF WIDE TEMPERATURE DOMAIN MINERAL ALLOYS - GUO XiaoE; ZHAO JinLu (Jixie qiangdu)
In order to improve the tribological performance of the parts of mine internal combustion engine in wide temperature domain, cobalt matrix composites with different proportions of solid lubricants（7%MoS2+7%ZnO, 9%MoS2+ 5%ZnO, 11%MoS2+ 3%ZnO） were prepared by hot pressing sintering technology. The tribological properties of the composites at room temperature, 200℃, 400℃, 600℃ and 800℃ were tested by high temperature friction and wear testing machine. The microstructure, phase composition and wear mechanism of the materials were studied. The results show that the three materials show similar trends of friction coefficient and wear rate. MoS2 effectively improves the tribological properties of composites in a wide temperature range. The frictional and anti-wear effect of ZnO mainly plays a role at 800℃. The tribological properties over a wide temperature range are attributed to the sulfide films at moderate and low temperatures and the oxide films composed of ZnO, Co2O3 and chromate at high temperatures. The wear mechanism is abrasive wear at low temperature and oxidation wear at high temperature. The results show that the materials containing 9%MoS2+ 5%ZnO exhibit the best tribological properties over a wide temperature range.